Factors that Determine Comprehensive Categorical Classification of EHR Implementation Levels - Soumya Upadhyay; William Opoku-Agyeman (SAGE Publishing, 2021)
Electronic Health Records (EHRs) have the potential to alleviate patient safety mistakes. Of the various levels of EHR, advanced or higher-level functionalities of EHR are designed to improve patient safety. Certain organizational and environmental factors may pose as barriers toward implementing all of the functionalities, leaving certain hospitals intermediate between basic and comprehensive levels of implementation. This study identifies a comprehensive categorical classification that includes hospitals that have functionalities between basic and comprehensive levels of EHR and determines the organizational and environmental factors that may influence hospitals to implement one or more combinations of these categories. A longitudinal panel design was used. Ordinal logistic regression with random effects model was fitted with robust cluster standard errors. Our sample consisted of non-federal general acute care hospitals utilizing a panel design from 2010 to 2016 with 17 586 hospital-year observations (or an average of 2600 hospitals per year). Larger size hospitals, ones with higher total margin, metropolitan and urban hospitals, system affiliated hospitals, and those in higher managed care penetration areas have higher odds of belonging in one of the higher categories of EHR implementation. Hospitals that can access a greater amount of human resources and financial assets from their environments, may implement higher levels of EHR. Initial and maintenance costs of EHR, interoperability issues, and inability to distribute high costs of training across facilities may stymie implementation of higher EHR functionalities. Policymaking to encourage competition among vendors may possibly lower the implementation price for hospitals with limited resources.